LASSUER -GRAHAM-LITTLE-PICCARDI SYNDROME - Sabia, Lívia Mendes (2014)
Lassueur Graham-Little-Piccardi syndrome is a rare dermatosis of unknown etiology that affects mainly women between 30 and 60 years old. It is characterized by the triad of multifocal scarring alopecia of the scalp, lichenoid follicular eruption and hypotrichosis of axillary and pubic regions. Anatomopathological examination revealed decrease in the number of hair follicles, upper perifollicular infiltrate and areas with fibrosis. Therapy is a challenge, with frequent relapses after local and systemic treatments. We report a typical case of this rare syndrome in a male patient of 46 years.